Pendidikan Karakter yang Menyenangkan (Studi di PAUD Shofa Azzahro) (PIAUD IAIN Kudus, 2017)
Character education should be instilled early on, because children PAUD especially still in the golden age stage. At this stage the child is very well developed character values. Optimal child development potential will be influential in the future. Character education implanted in early childhood must certainly remain fun, because children at this stage is still the stage of play and learning. Embedding character values is not rigid, familiarizing children praying before and after learning must have tucked into the planting of religious values. Embedding the values of honesty by telling the dogeng about honesty has tucked the planting of characters.